2020
DOI: 10.3168/jds.2019-17092
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and evaluation of lactic acid bacteria from indigenous raw milk for potential probiotic properties

Abstract: Raw milk contains wide microbial diversity, composed mainly of lactic acid bacteria (LAB), which are used as probiotics in both human and animal husbandry. We isolated, characterized, and evaluated LAB from indigenous Bangladeshi raw milk to assess probiotic potential, including antagonistic activity (against Escherichia coli O157: H7, Enterococcus faecalis, Salmonella Typhimurium, Salmonella Enteritidis, and Listeria monocytogenes), survivability in simulated gastric juice, tolerance to phenol and bile salts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
112
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 159 publications
(131 citation statements)
references
References 65 publications
16
112
2
1
Order By: Relevance
“…LAB usually produce antimicrobial compounds comprising organic acids, hydrogen peroxide, and bacteriocin, among others [41]. Sensitivity tests suggested that the CFS samples from our isolates did not contain any compounds of a proteinaceous nature [42]. It is reasonable to infer that the antibacterial activity of the studied CFS samples might be attributed to organic acids which can also play a role during growth in GI tract conditions.…”
Section: Discussionmentioning
confidence: 73%
“…LAB usually produce antimicrobial compounds comprising organic acids, hydrogen peroxide, and bacteriocin, among others [41]. Sensitivity tests suggested that the CFS samples from our isolates did not contain any compounds of a proteinaceous nature [42]. It is reasonable to infer that the antibacterial activity of the studied CFS samples might be attributed to organic acids which can also play a role during growth in GI tract conditions.…”
Section: Discussionmentioning
confidence: 73%
“…The lipid layer, which is thinner, causes the pores of the walls to shrink so that cell permeability is reduced and the extraction of intracellular components by acid cannot damage the lipid layer that is on the cell membrane. However, this lipid layer contains special proteins; some of the membrane proteins are enzymes, while others can bind to nutrients and transport them into the cells [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ability of a potential probiotic strain to tolerate or withstand intestinal bile salt is of immense importance to their survival and growth in the GIT; thus, it is a major requirement for probiotic selection. In the poultry GIT, the duodenum and cecum have a total bile salt concentration of 0.175 and 0.008% [ 7 ], and the bile salt concentration for humans’ ranges from 0.14 to 0.93 mM [ 26 ]. However, the average level of 0.3% bile salt has been considered in many studies as the threshold for bile salt tolerance of a potential probiotic [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations